2014
DOI: 10.1002/chem.201404638
|View full text |Cite
|
Sign up to set email alerts
|

New Synthesis of α′‐Hydroxydienones

Abstract: Herein, attempted oxidation of selected allenols with PCC affording α'-hydroxydienones rather than simple oxidation products is described. The formation of the products observed is rationalized via a series of sigmatropic shifts, followed by hydrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…A literature survey revealed that present methodology was not documented previously. However, a similar kind of transformation under PCC conditions [10] was observed by Mehta et al during the synthesis of secoprezizaane [10a] and Paterson et al during the synthesis of Jiadifenolide. [10b] We also found a few related transformations using iodine based reagents [11] which were unsuccessful on our substrate to furnish desired product 5 a.…”
supporting
confidence: 56%
“…A literature survey revealed that present methodology was not documented previously. However, a similar kind of transformation under PCC conditions [10] was observed by Mehta et al during the synthesis of secoprezizaane [10a] and Paterson et al during the synthesis of Jiadifenolide. [10b] We also found a few related transformations using iodine based reagents [11] which were unsuccessful on our substrate to furnish desired product 5 a.…”
supporting
confidence: 56%
“…The mechanism for this unexpected annulation cascade is not clear at present, but spectroscopic data and isolation of early intermediates suggest a Mannich addition followed by triflate elimination to form an allene ( A ). How the phenol oxygen atom is incorporated is not confirmed yet, but we are most intrigued by the possibility of the oxygen atom originating from the sulfinamide auxiliary via an intramolecular conjugated addition of the nucleophilc oxygen followed by in situ elimination of the C–N bond ( A to B ) . Intermediate B is expected to undergo a facile electrocyclization and air-oxidation to form the product ( 32 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The methodology was extended to a wide number of structures with different substituents, exhibiting moderate to excellent yields and excellent stereoselectivity. 78 …”
Section: Synthetic Utilitymentioning
confidence: 99%
“…One rare example of this kind of transformation using a different activated allene employs tosyl derivatives 18 . Treatment with n BuLi at low temperature yields the corresponding organolithium compound, which is reported to be trapped in the presence of different aldehydes generating α-allenols 19 (Scheme , reaction c) . A wide variety of aldehydes or ketones and arylsulfones are tolerated, although the challenging trisubstitution pattern around the allene skeleton should be already present in the starting material.…”
Section: Synthesis Of Allenolsmentioning
confidence: 99%